IMPLEMENTASI MANAJEMEN PERUBAHAN DALAM MENGEMBANGKAN BUDAYA ORGANISASI DI SMP NEGERI 36 KOTA BANDUNG - Wahyu Hidayat; Yara Tiarawati (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine the Implementation of Change Management and the steps taken by the School in developing an organizational culture at SMPN 36 Bandung. This type of research is qualitative with a descriptive approach. Research data collection techniques using research methods namely observation, interviews and documentation. The data analysis technique is by data reduction, data presentation, drawing conclusions. The results of this study indicate that the principal's steps in implementing change management in developing an organizational culture in students are starting from planning, implementing and supervising the culture that has been established jointly by the teacher and student councils. As for the form of organizational culture at SMPN 36 Bandung, namely the school continues to carry out positive cultures that are already running, especially in shaping student character, starting from morning greetings, morning religious culture which includes reading asmaul husna together, praying dzuha together, reading the Qur’an together , then literacy culture activities, fit and clean culture are carried out every Friday. All these positive activities are implemented at school. Based on this, it can be concluded that the Implementation of Change Management in developing the Organizational Culture of SMPN 36 Bandung has been going well. Judging from the existing changes, both in terms of time and means.